1986
DOI: 10.3382/ps.0651891
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Aflatoxicosis in Broiler Chickens

Abstract: The progression of aflatoxicosis was evaluated in young broiler chickens (Hubbard X Hubbard). The experimental design consisted of four dietary treatments of aflatoxin (0, 1.25, 2.5, and 5.0 micrograms of aflatoxin/g of feed, ppm) and 11 replicates of 10 broilers/replicate. The broilers were maintained in electrically heated batteries with feed and water available ad libitum from hatching to 3 weeks of age. The broilers were weighed, bled, killed by cervical dislocation, and necropzied at 3, 6, 9, 12, 15, 17, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
55
0
27

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 17 publications
18
55
0
27
Order By: Relevance
“…The decreased relative liver weights of our aflatoxin-fed poults (Table 1) is consistent with previous studies of domestic poults (Gumbmann et al, 1970;Weibking et al, 1994). Studies in chickens indicate that the liver is the organ most sensitive to the effects of aflatoxin (Huff et al, 1986). Reported alterations in weights of other organs vary, which previously has been speculated to be due to the different forms of aflatoxin and different concentrations of aflatoxin metabolites used in each study (Weibking et al, 1994).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The decreased relative liver weights of our aflatoxin-fed poults (Table 1) is consistent with previous studies of domestic poults (Gumbmann et al, 1970;Weibking et al, 1994). Studies in chickens indicate that the liver is the organ most sensitive to the effects of aflatoxin (Huff et al, 1986). Reported alterations in weights of other organs vary, which previously has been speculated to be due to the different forms of aflatoxin and different concentrations of aflatoxin metabolites used in each study (Weibking et al, 1994).…”
Section: Discussionsupporting
confidence: 79%
“…Reductions in serum triglycerides also have been reported in chickens with high levels of aflatoxin exposure (Huff et al, 1986). This is compatible with the compromised hepatic function and hepatocellular damage indicated in these wild turkey poults by hypoalbuminemia, hypoproteinemia, and increased aspartate aminotransferase activity.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In intoxicated broilers, no variations in serum cholesterol, triglycerides, calcium, or phosphorus concentrations were found, in agreement with other authors describing aflatoxicosis in 1-day-old chicks (Tung et al, 1972;Huff et al, 1986;Manning et al, 1990a,b). Nor did we find significant variations (P> 0.05) in any enzyme levels, in agreement with Ostrowski-Meissner (1984) in serum of chicks intoxicated by aflatoxins, indicating that enzyme levels do not provide a sufficiently precise diagnosis of aflatoxicosis.…”
Section: Discussionsupporting
confidence: 79%
“…Smith & Hamilton (1970) described an increase of relative liver weight during aflatoxicosis in broilers. Huff et al (1986) found in broilers, at the beginning of intoxication, liver atrophy, reflecting an inhibition of liver maturation in the early stages of aflatoxicosis and later hepatomegaly. A reduction of liver size in lambs intoxicated by 2.6 parts/10 6 of aflatoxin has been described (Harvey et al, 1991).…”
Section: Discussionmentioning
confidence: 99%